Rekonseptualisasi Epistemologi: Metode Islamisasi dalam Ilmu Psikologi Modern - Ussisa 'Alat Taqwa; Asep Awaludin; Jarman Arroisi (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
Modern psychology is often considered inadequate in addressing human psychological issues holistically due to its lack of spiritual dimension and an overemphasis on psychological aspects. This leads to the loss of essential direction and purpose in understanding human behavior. This study aims to explore the approach of Islamization as a solution to improve the shortcomings of modern psychology. The focus is on the reconceptualization of epistemology in modern psychological science through the integration of Islamic values with modern psychological concepts and theories. This research uses a qualitative approach by collecting data from various relevant literature sources on modern psychology and Islam. The data are analyzed thematically to identify patterns and themes that emerge in the context of the epistemology and methodology of psychology. The results of the study indicate that Islamization in modern psychological science can result in a reconceptualization of epistemology that considers the spiritual and psychological dimensions of humans in a balanced manner. By integrating Islamic principles into psychological theories and methods, this approach provides a more comprehensive understanding of human behavior. Consequently, Islamic psychology becomes a significant alternative in healing and comprehensively understanding human psychological issues, as well as restoring essential direction and purpose in modern psychological science. This research contributes valuable insights into the development of more inclusive and holistic psychological theories and practices.